Effect of Routing Flexibility on the Performance of Order Release Policies in a Flexible Job Shop with Sequence-Dependent Setup Time: A Simulation Study. Issue 1 (2nd January 2023) - Rani, Sushma; Jain, Ajai; Angra, Surjit
ABSTRACT: Order review and release (ORR) in a flexible job shop considering sequence-dependent setup time (SDST) is a complicated job shop problem. Routing flexibility helps in increasing the flexibility of the system by providing alternative routes to jobs. This research work assesses the effect of routing flexibility on order release policies in a flexible job shop considering SDST within a stochastic and dynamic (SCDM) manufacturing environment. In this study, five order release policies, viz., Corrected Aggregate Load Approach (CALA), Aggregate Workload Trigger (AGGWLT), Corrected Workload Trigger (CorrWLT), Work Center Workload Trigger (WCWLT), and Lancaster University Management School Corrected Order Release (LUMSCOR), are considered with planned release date sequencing rule. Four performance measures are considered in the present research work, i.e., mean throughput time, mean lead time, mean tardiness, and total setups. For experimental purposes, a simulation model is developed with six routing flexibility levels with the help of Promodel® software. Results indicate that the performance of all ORR policies can be improved by considering routing flexibility along with it. For a given ORR policy, as routing flexibility increases, there is a decrease in system performance measures up to a certain level, and after that, it starts increasing. Thus, routing flexibility has an optimum level. The least value of workload trigger level for all ORR policies provides the best results for mean throughput time performance measure. Further, as the workload trigger level increases, the best results are obtained for the other three performance measures except the mean throughput time. Graphical abstract: uf0001